Pour une archéologie des peintures murales, la Chasse royale de la chapelle Sainte-Radegonde à Chinon (Indre-et-Loire) : étude technique et résultat des datations par le 14C - Amaëlle Marzais (Revue Archéologique du Centre de la France)
The thematic exploration and analyses financed by the Regional Archaeology Department in 2019 allow us to address neglected aspects of the Royal Hunt, painted on the north wall of the nave of the Sainte-Radegonde Chapel in Chinon (Indre-et-Loire). The iconography had been discussed on several occasions since the discovery of this painting in 1965, but the technical aspects, as the implementation processes, tools, materials and gestures used, had not yet been studied. Thus, by focusing on two of the five horsemen, the successive application of the colouring stages can be identified and restored. The dating of this painting, debated since 1990, had been established in the historiography on the basis of iconographic and, more rarely, stylistic clues, and varies between the end of the 12th and the first years of the 13th century. In 2019, the use of 14C dating of charcoal taken from the painted coating has made it possible to reconsider the dating of this work and to situate its execution between 1150 and 1200. This dating provides a chronological framework for the paintings, which are at the crossroads of technical and stylistic changes. The painters of these works, including the Royal Hunt, used a technique that was partly based on fresh plaster and motifs from the Romanesque vocabulary, combined with a style that already showed marked 13th century characteristics such as a thick black ring and the gradual abandonment of modelling on the face.